Preparation, characterization and properties of the ternary composite β2-SiW11/polyaniline/graphene oxide. Issue 17 (26th January 2022) - Cao, Rui; Ma, Ronghua; Wen, Qi; Zhang, Cheng-Li; Yang, Ming-Rui
Abstract: The composites β2 -SiW11 /GO and β2 -SiW11 /PANI/GO were prepared by using graphene oxide as a carrier. Properties of the composites were characterized by UV-visible spectroscopy (UV-vis), infrared spectroscopy (FT-IR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM-EDS), transmission electron microscopy (TEM), N2 adsorption desorption and thermal gravimetric analysis. Properties of the composites were investigated by using methyl violet simulated industrial wastewater. The results showed that this composite had photocatalytic activities for many dyes, and the activity was higher than that of Degussa P25(TiO2 ). The photocatalytic performance of β2 -SiW11 /PANI/GO had a higher activity than that of PANI, β2 -SiW11 and β2 -SiW11 /GO, with photodegradation reaching 95.98% under 30 W ultraviolet light for 150 min. The reaction kinetics for photocatalytic degradation of methyl violet followed a first-order process. The prepared composite was recyclable and the performance remained good. The possible mechanism of photocatalytic activity of dopant material is discussed and schematized. Graphical Abstract: UF0001